Factors Affecting Climate-Smart Agriculture Practice Adaptation of Farming Households in Coastal Central Vietnam: The Case of Ninh Thuan Province - Duc Truong, Dinh; Tho Dat, Tran; Huy Huan, Le (Frontiers in Sustainable Food Systems, 2022)
Agriculture is a sector with a long tradition and an important contribution to economic growth in Vietnam, providing food security and generating revenue for the country's exports. However, agricultural activities in Vietnam are significantly affected by climate change. In Vietnam, the central coastal area in general and Ninh Thuan province in particular are the most vulnerable areas to natural disasters. In that context, climate-smart agriculture (CSA) is a strategy to creating agricultural solutions for securing climate change sustainable food security and adaptation. This study has two main objectives: to assess the farmers' awareness of the disasters and impacts on agricultural production and CSA practices to adapt to climate change in Ninh Thuan province. The study also analyzes the factors affecting the decision to apply CSA practices of the households. The study has conducted focus group discussion, in-depth interview and survey of 436 households in 3 districts of Ninh Thuan province to collect data. Research results show that people have a high awareness of natural disasters, their impact on agricultural livelihoods and the adaptation solutions are applied including applying conservation farming techniques, minimal tillage, intercroppin, crop rotation , crop transformation and the use of plant varieties that are resistant to adverse conditions. Binary logit regression analysis showed that age, education level, household income, membership of local associations, training attendance and support policies were the variables that significantly influenced the decision to apply. CSA of farmers. Challenges for CSA adoption include lack of capital, information, technical support and land ownership institutions in Vietnam. The study also made recommendations to promote CSA in Vietnam, including reforming the legal system, strengthening agricultural extension services, and providing technical and capital support to farmers.